THE SPECIFICITY OF THE PROCESS OF STRATEGICAL PLANNING OF «RUSSIAN HIGHWAYS» STATE COMPANY - A. Alenkina (Вестник университета)
The aim of this work is to research the influence of industry’s specificity to the process of strategical planning of «Russian Highways» State Company. Methodologically researching consists in illustration of seven processes of strategic management on the example of «Russian Highways» State Company. The system of strategical planning documents of State Company was analyzed. The distinctive feature of strategical panning process of road building was discovered. It is in the necessity of consideration of federal and regional programs of social and economic development, schemes of territorial planning and other documents of spatial development of Russia in the process of planning of road building.